The Usage of Block Average Intensity in Tamper Localization for Image Watermarking - Liew, Siau-Chuin; Jasni, Mohamad Zain (IEEE, 2011)
Tamper localization capable image watermarking scheme is able to detect the location of manipulated areas, and verify other areas as authentic. The usage of block average intensity in the tamper localization process is one of the popular techniques due to its easy implementation. The effectiveness of using average intensity for tamper localization had not been properly tested. Experiments were performed using a tamper localization watermarking scheme for medical image which is based on block average intensity. The results shows that the tamper localization process will fail in certain conditions and caused some tampering left undetected.